The Effect Of Environmental Accounting And CSR Disclosures On The Financial Performance Of Manufacturing Companies Listed On The IDX In 2019-2023 - Nasution, Aisyah Maulidina; Gusrianti, Gusrianti; Dewi, Sandra; Isriani, Rahmi (Al-Sharf: Jurnal Ekonomi Islam, 2026)
This study aims to investigate the effect of environmental accounting disclosure and corporate social responsibility (CSR) on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. A quantitative approach was employed as the methodological basis of the analysis. The findings reveal that, simultaneously, environmental accounting and CSR have a significant impact on corporate financial performance. However, when examined partially, the effects of each variable exhibit contrasting directions, with variable X1 showing a significant positive effect, while variable X2 demonstrates a negative effect. These results highlight the importance of integrating environmental and social issues into the corporate reporting framework as a strategic step toward sustainability, while also serving as a reference for regulators in strengthening policies on transparency and accountability in non-financial reporting.